Efektivitas Program Garda Ampuh dalam Mengurangi Angka Putus Sekolah di Kecamatan Kabat Kabupaten Banyuwangi - Dian Ayu Puspayanti (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to describe the effectiveness of the implementation of the Garda Ampuh Program in reducing school dropout rates in Kabat District, Banyuwangi Regency. The approach used in this research is descriptive qualitative with data collection techniques through overt or covert observation, semi-structured interviews and documentation. The research location was at the Education Office of Banyuwangi Regency and the Regional Office of Kabat Sub-district. Informants consisted of program implementers, education units, student guardians and program recipient students. The results of this study indicate that the implementation of the Garda Ampuh Program is quite effective in reaching children at risk of dropping out of school. The effectiveness of the program can be seen from several aspects, namely: understanding of the program, on time, on target, achieving goals and real changes. However, there are still obstacles in the form of delays in fund disbursement and the verification process at the non-formal level. Thus, the Garda Ampuh program has a positive impact in reducing the dropout rate in Banyuwangi Regency, but it needs to be evaluated on an ongoing basis through strengthening the coordination system and increasing the capacity of program assistants.
Reaploud Repository February 2026_Hasyim
Keywords: Effectiveness; Garda Ampuh; School Dropouts